A guide on transnasal endoscopy: setting up a pediatric unsedated endoscopy program - Friedlander, Joel A.; Leinwand, Kristina; Bhardwaj, Vrinda; Nguyen, Nathalie (Frontiers in Pediatrics, 2024)
Background: Unsedated transnasal endoscopy is becoming an increasingly popular option for the evaluation of upper gastrointestinal tract disorders in adults and children worldwide. This innovative technology has transformative potential as it provides for a more efficient, safe, and cost-effective method for endoscopy and reduces the risks associated with anesthesia, which is particularly relevant in pediatrics as endoscopy is commonly done under general anesthesia or conscious sedation. The aim is to address knowledge gaps amongst pediatric gastroenterologists who may be considering the development of a TNE program, detailing how to implement sedation-free TNE into practice for pediatric patients and current and forthcoming technologies. Methods: We conducted a comprehensive review of current literature and collection of data from experts and clinicians in the field on how sedation-free programs were started and being conducted. We aimed to collate the data to provide a guide to address knowledge gaps with a focus on setting up and starting a sedation-free endoscopy program. Results: Here in, we provide a detailed guide for implementing a sedation-free endoscopy program in pediatrics including design and layout of a TNE unit, special staffing needs, equipment, current and forthcoming technologies, financial considerations and training considerations. We highlight special considerations that are relevant in pediatrics incorporating distraction or dissociation techniques such as Virtual Reality Systems, developmentally appropriate preparation for children, and topical analgesia. Conclusion: Sedation-free endoscopy is a rapidly growing option for pediatric patients. Development of an unsedated pediatric endoscopy program will improve patient care, decrease the need for anesthesia, provide a lower cost and safe alternative to traditional sedated endoscopy, and is a viable component to a pediatric gastroenterology practice.